PENGARUH MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN PADA PT. HADJI KALLA TOYOTA CABANG URIP SUMOHARDJO MAKASSAR - Surya Kelana Basri; Agussalim Rahman (Jurnal Edueco, 2023)
The purpose of this study was to determine the effect of motivation and discipline on employee performance at PT. Hadji Kalla Toyota Urip Sumohardjo Branch. The type of data used in this research is qualitative and quantitative data. The data sources used in this research are primary and secondary data. The analytical method used is descriptive analysis and statistical analysis. The results showed that motivation and discipline both partially and simultaneously had a positive and significant effect on the performance of employees at PT. Hadji Kalla Toyota Urip Sumohardjo Branch.